«Quiet flows the Don» by M.A. Sholokhov: evolution of interpretation by Chinese critics (Proceedings of Southern Federal University. Philology, 2015)
Tsytsenko I.I., Sun Hatszya (Southern Federal University, Rostovon-Don, Russian Federation)This article attempts to analyze and give a general idea about the main approaches to the study of “Quiet Flows the Don” in China from 1949 to the 2000s, which is essential for the reconstruction and the description of the international reception of Mikhail Sholokhov’s creativity in general, and also allows to see the dynamics of the perception process of the individual specific cultural dialogue between Russia and China in the XX century, due to the political, historical, aesthetic and linguistic factors.The development of “Quiet Flows the Don” in Chinese literary criticism has two main stages: 1949-1985s (one-sided interpretation of “Quiet Flows the Don” in the context of political culture) and the 1985-2000s (a scientific approach in the context of a non-political culture). Each of these stages considers separate periods marking the specifics of the study related to the specific feature of China’s historical and cultural situation, analyzes the most interesting point of view of Chinese researchers. Great attention is given to the issues that were discussed in the Chinese literary criticism and topical issues that reflect the experience of revolution and civil war, the question about the main character of the epic novel and the origins of the tragedy and artistic skill of Sholokhov.Key words: reception, art world, paradigm of socio-cultural factors, ideological and artistic humanism, concept of the character.DOI: 10.18522/1995-0640-2015-4-26-35